Islamic Religious Education Methods for Inclusive Classes at Madrasah Aliyah Muhammadiyah 1 Ponorogo - Nurjan, Syarifan; Oktaviani, Dewi; Tajab, Muh (MUADDIB Jurnal Kependidikan dan Keislaman, 2024)
This study examines the methods of Islamic Religious Education (PAI) implemented in inclusive classes at Muhammadiyah 1 Ponorogo High School. This topic is significant as inclusive education demands teaching strategies that accommodate the diverse abilities of students, including those with special needs, ensuring equitable access to religious education. The aim of this research is to analyze suitable PAI teaching methods for inclusive classes and assess their effectiveness in improving students’ understanding of religious material. This study employs a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews with teachers and students, and document analysis related to the implementation of PAI in inclusive classes. A participatory approach is also utilized to explore the experiences and challenges faced by teachers in teaching inclusive classes. The findings reveal that individual needs-based teaching methods, such as differentiated instruction, curriculum adaptation, and the use of interactive learning media, greatly assist students with special needs in comprehending PAI material. Teachers play a critical role in creating an inclusive and supportive learning environment. These methods have been proven to enhance student participation in the learning process and facilitate a deeper understanding of religious teachings. The implications of these findings emphasize the importance of developing teachers’ capacities to manage inclusive classes, particularly in PAI subjects. This research also contributes to improving inclusive education practices in Indonesia by providing recommendations for madrasahs and other educational institutions to pay greater attention to the needs of inclusive students in religious education processes.